Pengaruh Motivasi terhadap Produktivitas Kerja: Studi Kasus pada PT X Bandung - Hamali, Arif Yusuf (Journal the Winners: Economics, Business, Management, and Information System Journal, 2013)
This research was conducted at PT X Bandung, aimed to determine how motivation and employee productivity and also to know the influence of motivation to work productivity at PT X Bandung. Respondents of this research are 50 with census sampling technique. The method used is descriptive and associative, which tests the connection using the Spearman rank correlation analysis, and also done to determine the accuracy the measurement using by the validity and reliability test. The results of the validity and reliability test of variables X and Y are valid and reliable. Calculations were performed using SPSS software ver.19. The results of this study showed that motivation is in the category of quite good and work productivity is in the category of good. The results showed the influence of motivation to employeeâ€™s workÂ  productivity at PT X Bandung with a correlation coefficient = 0.510. Based on the criteria Champion, this relationship is in the criteria of fairly strong relationship. The results of this calculation showed the coefficient of determination = 26.01%. It showed that the the hypothesis is proved: there is the influence of motivation to work productivity at PT X Bandung.